GE_GERICHTE P/3848/2022 vom 8. Mai 2024 - GE Cour de justice (2024)
CLASSEMENT DE LA PROCÉDURE;FRAIS DE LA PROCÉDURE;INDEMNITÉ(EN GÉNÉRAL);MOTIVATION DE LA DÉCISION;DROIT D'ÊTRE ENTENDU | CPP.421; CPP.423; CPP.426; CPP.429; CPP.430; Cst.29